Miss South Carolina: a pragma-dialectical analysis - Joannon, Cristóbal (Onomázein, 2010)
This text presents an argumentative analysis of a very well-known interaction –a so-called “YouTube phenomenon”– that a candidate of a Beauty Contest gave when she was asked about the reason why a fifth of American people is not able to locate the U.S. in a World map. This analysis uses the Pragma-dialectical approach to argumentative discourse in its dialectical and rethorical dimensions, and shows what powerful it is in order to decipher and evaluate the argumentative structure of a muddled discourse.